The Effect of Role Playing Methods on Student Learning Outcomes in Civic Education at Elementary Schools - Hardiansyah, Framz; Hasanah, Jamilatul; Dinaniyah, Nur; Sutriyani, Sutriyani; Zakiyah, Zakiyah (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the effect of the role-playing method on students' learning outcomes in Civics Education (PPKn) at the elementary school level. The research employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 25 students. Data collection was carried out by administering learning outcome tests before and after the implementation of the role-playing method. Data analysis was conducted using a paired sample t-test to examine the differences in learning outcomes before and after the method was applied. The results of the study showed a significant improvement in students' learning outcomes after the implementation of the role-playing method. A total of 90% of the students showed an increase in scores above the Minimum Mastery Criteria (KKM). This indicates that the role-playing method has a positive effect on students’ learning outcomes in Civics Education.